Relevansi Teori Belajar Konektivisme dalam Disrupsi Teknologi dan Artificial Intelligence Era - Gunawan, Arie Indra; Rizaldy, Fikry; Afifah, Nurul; Nuraryanti, Asti Nur; Utama, Dian Herdiana (Jaanur Elbarik Indonesia, 2025)
The process of revolutionizing human knowledge has finally arrived at a concept that describes the relationship between human learning and open access to knowledge that can be obtained from various sources. Connectivism emerged as a network learning theory, this theory is a learning theory developed for the information technology environment. This study was conducted by collecting library data both from books and from research results. The collection of data obtained is reviewed in a structured manner and records important matters which are then processed to become information. The findings from the results of the study reveal that Connectivism is a learning theory that emphasizes the importance of the relationship between humans, technology, and information in the learning process. Connectivism integrates advances in learning and takes into account learner behavior in the